'I Have Brothers and Sisters in Those Parties': More on the 'Conscientious Sister of the Lunenburg Letter' - Matson, David Lertis (Stone-Campbell journal, 2011)
This paper continues the investigation of a previously published article in the Stone-Campbell Journal that identified the author of the pseudonymous Lunenburg Letter as Louisa Ann Anderson, wife of Albert Anderson and ardent supporter of Dr. John Thomas, eventual founder of the Christadelphians. In her letter to Alexander Campbell, Louisa mentions that she has brothers and sisters among the sects with whom she refuses even to pray. Some of these individuals, previously unknown to all but perhaps the most conscientious historian, now emerge onto the historical stage for the first time as participants in the historical family drama that is the Stone-Campbell Restoration Movement.